Science 3-13 : the past, the present, and possible futures - Warwick, Paul, 1956-; Linfield, Rachel Sparks (Primary directions series., 2000)
Explores some of the historical antecedents of the current position of science in the lives of younger children. Current teaching practice is examined and on this basis speculations are made about the future direction of this subject.